For and against method : including Lakatos's lectures on scientific method and the Lakatos-Feyerabend correspondence - Lakatos, Imre, 1922-1974 (University of Chicago Press, 1999)
The work that helped to determine Paul Feyerabend's fame and notoriety, Against Method, stemmed from Imre Lakatos's challenge: "In 1970 Imre cornered me at a party. 'Paul, ' he said, 'you have such strange ideas. Why don't you write them down? I shall write a reply, we publish the whole thing and I promise you--we shall have a lot of fun.' " Although Lakatos died before he could write his reply, For and Against Method reconstructs his original counter-arguments from lectures and correspondence previously unpublished in English, allowing us to enjoy the "fun" two of this centu